The effects of low frequency sound on the levels of activation - Kasprzak, Cezary (Archives of Acoustics, 2007)
The paper summarises the research data showing how low frequency sound affects the level of activation in humans. Activation levels were measured with the use of the self-assessment questionnaire, known as the Activation-Deactivation Adjective Check List (AD ACL). The research program involved three independent stages and three types of acoustic stimuli were applied. The acoustic stimulus applied in the first stage had frequency f = 7 Hz, sound pressure level SPL = 120 dB (HP). In the second stage participants were exposed to an acoustic stimulus f = 18 Hz, sound pressure level SPL = 120 dB (HP). In the third stage a acoustic stimulus was applied f = 40 Hz, sound pressure level SPL = 110 dB (HP). The exposure time in each experiment was constant (20 min). Results indicate a statistically significant increase of the deactivation – sleep effect following the low-frequency sound exposure.